Kontribusi Islam terhadap Sains Manajemen - Salamuddin Salamuddin; Sartika Hutasuhut; Muhammad Isa; Yulita Suyatmika (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Science is a systematic effort to create, construct and organize knowledge to understand the universe. Management is the process of planning, organizing, directing and controlling. When viewed from the perspective of management as a science (science) and as an art. So management is both a science and an art. Why is it called that because the two cannot be separated. Management as a science, because it has been studied for a long time, and has been organized into a theory. This is because in it explains the symptoms of management, these symptoms are then investigated using the scientific method which is formulated in the form of principles that are embodied in the form of a theory. Keywords: Islamic scholar, science, management